Efektivitas Ekstrak Etanol Daun Ciplukan (Physalis angulata L.) Terhadap Penurunan Kadar Trigliserida Pada Mencit (Mus musculus) - Rafsanjani, Arief; Salsabila, Aulia; Yuliana, Tri Puspita (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Hypertriglyceridemia is a condition when triglyceride levels in the blood increase. High triglyceride levels can cause atherosclerosis, which is a risk factor for cardiovascular disease. The ciplukan plant contains chemical compounds, namely flavonoid compounds. Flavonoid compounds can reduce triglyceride levels by increasing the activity of the lipoprotein lipase enzyme. This research aims to determine the potential of Ciplukan (Physalis angulata L) leaf extract in reducing triglyceride levels in mice (Mus musculus). This type of research is experimental research with a Pretest-Posttest Control Group design. This study consisted of a negative control group, positive control, treatment dose I (2.8 mg/20 gr BW), dose II (5.6 mg/20 gr BW), and dose III (8.4 mg/20 gr BW ). Based on the results of the pne-way ANOVA analysis test, it showed significant differences between the negative control group and the positive control group, treatment dose I, dose II, and dose III with a significance value of p<0.05. The conclusion of this research is that the ethanol extract of ciplukan leaves has the potential to reduce triglyceride levels in mice induced by quail egg yolk.